2014
DOI: 10.1002/jsfa.6825
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-manure compost in conjunction with pyroligneous solution alleviated salt stress and improved leaf bioactivity of maize in a saline soil from central China: a 2-year field experiment

Abstract: A combined amendment of crop straw biochar with manure compost plus pyroligneous solution could help combat salinity stress to maize and improve productivity in saline croplands in arid/semi-arid regions threatened increasingly by global climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(124 citation statements)
references
References 29 publications
11
109
2
2
Order By: Relevance
“…Biochar, the product of different biomasses can provide an alternative sources of long-term C storage in soil to minimize climate variation by an enhancement in the biogenic C collection, decrease greenhouse gas emissions (Ubando et al 2014), restore soil fertility (Novak and Busscher 2013), amend soil physical properties such as pH, pore structure, surface area, and mineral matter (Jaafar et al 2014), enhance crop yield and productivity (Chintala et al 2014;Lashari et al 2014), and reduce N emission and leaching (Spokas et al 2012). Examples of the specific biochar properties accounted for these benefits are summarized in Table 1.…”
Section: Biochar Benefitsmentioning
confidence: 99%
“…Biochar, the product of different biomasses can provide an alternative sources of long-term C storage in soil to minimize climate variation by an enhancement in the biogenic C collection, decrease greenhouse gas emissions (Ubando et al 2014), restore soil fertility (Novak and Busscher 2013), amend soil physical properties such as pH, pore structure, surface area, and mineral matter (Jaafar et al 2014), enhance crop yield and productivity (Chintala et al 2014;Lashari et al 2014), and reduce N emission and leaching (Spokas et al 2012). Examples of the specific biochar properties accounted for these benefits are summarized in Table 1.…”
Section: Biochar Benefitsmentioning
confidence: 99%
“…Lashari et al (2015) suggested that biochar might contain significant amounts of soluble P and K, contributing to plant-available nutrient pools upon incorporation in the soil. Although addition of urea N has been reported to enhance soil acidification in the microsites, application of biochar can buffer the N acidification effect and minimise pH changes (Xie et al 2013).…”
Section: Available Nutrients (N P K)mentioning
confidence: 99%
“…Particularly, if biochar, a stable C-rich solid residue, is returned to the same field where residues would have been removed for pyrolysis, this process may return many nutrients, and improve soil properties such as soil bulk density, water holding and cation exchange capacity, favouring the retention of water and nutrients (Zheng et al 2013). Further, biochar application together with chemical fertilizers has been shown to increase agronomic benefits in terms of crop production especially in soils with low fertility, either by acting as a direct source of nutrients or by enhancing nutrient availability due to improvements in soil physical, chemical and biological properties (Lashari et al 2015). For example, combined application of biochar and N fertilizer has been found to have positive impacts on soil functions, and crop N uptake and productivity (Laird et al 2010;Jeffery et al 2011;Lori et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…production. There were increasing evidences suggested that biochar application could help combat salinity stress to plant and improve productivity in saline croplands (Drake et al, 2015;Lashari et al, 2015;Hammer et al, 2014). Akhtar et al (2015) have reported that incorporation of biochar into salt-affected soil could alleviate salinity stress mainly because of its high salt adsorption potential, decreasing osmotic stress by enhancing soil moisture content, and releasing mineral nutrients.…”
Section: −1mentioning
confidence: 99%